Embeddings of mappings via products and universal mappings - Megaritis, A. C. (Topology Proceedings, 2025)
In [16] S. D. Iliadis introduced the notion of a universal mapping for a given class of continuous mappings and proved in a unified way the existence of universal elements for many classes of mappings. In this paper, we construct universal mappings for several classes of continuous mappings using embedding theorems for mappings and a topological method related to [4].